Analysis of venom gland transcriptomes from two Tesseliconus species, Conus eburneus and Conus tessulatus, reveals inter- and intra-specific variations in conopeptide diversity and expression as well as putative novel gene superfamilies and disulfide-poor venom components - Tablizo, Francis A.; Masacupan, Dan Jethro M.; Lluisma, Arturo O. (Frontiers in Marine Science, 2025)
The Conus subgenus Tesseliconus, whose members are believed to be primarily worm-hunters, phylogenetically clusters closely with piscivorous groups relative to most other vermivorous subgenera. A previous study even documented the Tesseliconus species C. tessulatus to opportunistically prey on fish. Here, we identified and analyzed putative conopeptide sequences from the venom gland transcriptome of C. tessulatus and its sister species C. eburneus. From the set of assembled sequences with predicted complete coding sequences, we identified 260 C. ebureneus and 339 C. tessulatus transcripts for which assignment to a conopeptide gene superfamily and/or cysteine framework was possible. In addition, we identified over 50 transcripts per species that are highly similar to previously reported disulfide-poor conopeptides. Agglomerative clustering (75% similarity threshold) of the predicted signal sequences revealed the presence of 18 possibly novel gene superfamilies, alongside 10 known gene superfamily clusters. Inter- and intra-species variations in conopeptide diversity and expression were also observed, hinting to a number of potential but not necessarily exclusive scenarios. In particular, we hypothesize that the Tesseliconus species investigated in this study might be targeting a more diverse prey type than previously thought, and that individuals even of the same species may exhibit subtle differences in prey preference that allows them to better coexist within a given environment.